APPLICATION OF PROBLEM-BASED LEARNING TO IMPROVE STUDENT MOTIVATION AND LEARNING OUTCOMES ASSISTED BY WORDWALL - Frada, Titis Wilianti; Gunawan, Gunawan; Untarti, Reni; Kusuma, Jaka Wijaya; Ristianto, Meiga; Vertikawati, Ratna (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to determine student motivation and learning outcomes in applying project-based learning (PBL) assisted by Wordwall media. This type of research uses classroom action research (PTK). The study subjects were grade V students of SDN 1 Kedungbanteng, totalling 31 people. According to Kemmis and Mc Taggart, this research design refers to the Classroom Action Research (PTK) model; this research data collection technique uses observation, questionnaires and tests. The data analysis technique uses qualitative data analysis and quantitative data analysis. The results showed increased motivation and learning outcomes in PKN lessons using problem-based learning (PBL) through wordwall media. The study results were the results of the learning motivation questionnaire showing that the average class of students in cycle I was 61.69% in the medium category. In contrast, it increased by 11.09% in cycle II to 72.78%. The application of the problem-based learning (PBL) model through word wall media also improves student learning outcomes from before action (pretest) to the given action (posttest). Based on the results of the pretest scores, students showed 32.2% completeness, then the given action in cycle I increased to 45.16% and in cycle II increased to 87%. Based on the criteria set, problem-based learning (PBL) through wordwall media has met the predetermined standards of>70%.